2019
DOI: 10.1051/matecconf/201930005002
|View full text |Cite
|
Sign up to set email alerts
|

Blind prediction of FRP repairs for multiaxial fatigue cracks on Hydraulic Steel Structures

Abstract: Currently, over 80% of the navigation steel structures (NSS) within the United States' inland waterway system have reached or exceeded their useful design life. Age has caused deterioration of the design boundary conditions (e.g. diagonal relaxation and quoin block deterioration) leading to overloads and causing multi-axial fatigue cracking. Furthermore, corrosion and deterioration of the protective system accelerate the fatigue crack growth rate. This paper presents numerical experiments to evaluate the viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Experimental and analytical studies on investigating crack growth of adhesively repaired steel panels were conducted on flat steel specimens and have shown an increase in fatigue life in comparison to the unrepaired specimens (Young and Roore 1992;Colombi et al 2003;Jones and Civjan 2003;Duong and Wang 2004;Yue et al 2004;Hansen et al 2007;Liu et al 2009). Very few studies have been conducted on fatigue crack propagation in CFRP-repaired large-scale specimens representing real structural members (Bassetti et al 1999;Mertz et al 2002;Tavakkolizadeh and Saadatmanesh 2003;Jiao and Zhao 2004;Shield et al 2004;Vatandoost 2010;Kim and Harries 2011;Mahmoud and Riveros 2013;Mahmoud and Riveros 2014;Riveros and Lozano 2019;Riveros et al 2018). Although in some of the large-scale studies the conclusion on fatigue life improvement is not clearly discussed, it can be generally concluded that a three-to seven-fold increase in fatigue life was observed for retrofitted specimens when compared to their un-retrofitted counterparts.…”
mentioning
confidence: 99%
“…Experimental and analytical studies on investigating crack growth of adhesively repaired steel panels were conducted on flat steel specimens and have shown an increase in fatigue life in comparison to the unrepaired specimens (Young and Roore 1992;Colombi et al 2003;Jones and Civjan 2003;Duong and Wang 2004;Yue et al 2004;Hansen et al 2007;Liu et al 2009). Very few studies have been conducted on fatigue crack propagation in CFRP-repaired large-scale specimens representing real structural members (Bassetti et al 1999;Mertz et al 2002;Tavakkolizadeh and Saadatmanesh 2003;Jiao and Zhao 2004;Shield et al 2004;Vatandoost 2010;Kim and Harries 2011;Mahmoud and Riveros 2013;Mahmoud and Riveros 2014;Riveros and Lozano 2019;Riveros et al 2018). Although in some of the large-scale studies the conclusion on fatigue life improvement is not clearly discussed, it can be generally concluded that a three-to seven-fold increase in fatigue life was observed for retrofitted specimens when compared to their un-retrofitted counterparts.…”
mentioning
confidence: 99%